The impact of marriage on breastfeeding duration: examining the disproportionate effect of COVID-19 pandemic on marginalized communities - Anna Charlotta Kihlstrom; Tara Stiller; Nishat Sultana; Grace Njau; Matthew Schmidt; Anastasia Stepanov; Andrew D. Williams (International Breastfeeding Journal)
Abstract Background Marriage promotes breastfeeding duration through economic and social supports. The COVID-19 pandemic disproportionately affected marginalized communities and impacted women’s employment and interpersonal dynamics. This study examined how marriage affects breastfeeding duration across socioeconomic and racially minoritized groups during COVID-19, aiming to inform social support strategies for vulnerable families in public health crises. Methods For this cross-sectional study, data were drawn from the 2017–2021 North Dakota Pregnancy Risk Assessment Monitoring System (weighted n = 41433). Breastfeeding duration was self-reported, and 2-, 4-, and 6-month duration variables were calculated. Marital status(married, not married) and education (< high school education, ≥high school education) were drawn from birth certificates. Income (≤ US$48,000, > US$48,000) and race/ethnicity (White, American Indian, Other) were self-reported. Infant birth date was used to identify pre-COVID (2017–2019) and COVID (2020–2021) births. Logistic regression estimated odds ratios and 95% confidence intervals for the association between marital status and breastfeeding duration outcomes. Models were fit overall, by COVID-19 era and by demographic factors. Lastly, demographic-specific models were further stratified by COVID era. Models were adjusted for maternal health and sociodemographic factors. Results Overall, married women consistently had 2-fold higher odds of breastfeeding across all durations during both pre-COVID and COVID eras. Pre-COVID, marriage was a stronger predictor for all breastfeeding durations in low-income women (4-month duration OR 4.07, 95%CI 2.52, 6.58) than for high-income women (4-month duration OR 1.76, 95%CI 1.06, 2.91). Conversely, during COVID, marriage was a stronger predictor of breastfeeding duration for high-income women (4-month duration OR 2.89, 95%CI 1.47, 5.68) than low-income women (4-month duration OR 1.59, 95%CI 0.80, 3.15). Findings were similar among American Indian women and those with less than high school education, in that both groups lost the benefit of marriage on breastfeeding duration during the COVID-19 pandemic. Conclusion Marriage promotes breastfeeding duration, yet the observed benefit was reduced for low-socioeconomic and racially minoritized populations during the COVID-19 pandemic. These observations highlight the disproportionate impacts low-socioeconomic and racially minoritized populations face during public health crises. Continued research examining how major societal disruptions intersect with social determinants to shape breastfeeding outcomes can inform more equitable systems of care.